Evapotranspiration in a prairie ecosystem: effects of grazing by cattle - Bremer, Dale J.; Auen, Lisa M.; Ham, Jay M.; Owensby, Clenton E. (My University, 2009)
Grazing by ungulates is common in grasslands and may influence evapotranspiration (ET). The Bowen ratio energy balance method was used to measure ET from grazed (GR) and ungrazed (UGR) tallgrass prairie in northeastern Kansas, USA. Yearling steers were stocked on the GR site from day of year (DOY) 128 to 202, 1999, and ET data were collected from DOY 141 to 295. Grazing reduced ET by 28% between DOY 179 and 207; mean ETs were 3.6 mm d[superscript -1] (GR) and 5.0 mm d[superscript -1] (UGR). During that period, leaf area index (LAI) averaged 78% lower on the GR site and below-normal precipitation kept soil dry near the surface; hence transpiration and evaporation of water from soil decreased. Lower ET during that period conserved soil water in the 0-0.30 m profile on the GR site. Prior to that (e.g., DOY 152 to 179), ET was similar between treatments despite an average 70% lower LAI on the GR compared with the UGR site. Above-normal precipitation during that period probably maintained high evaporation of water from soil, thereby compensating for reductions in transpiration (via LAI removal) on the GR site. Cumulative ETs during the 155-day study were estimated at 526 and 494 mm on the UGR and GR sites, respectively. Thus, grazing reduced seasonal ET by 6.1%. Late in the study, ET was higher on the GR site, despite a lower LAI compared with the UGR site. Younger leaves in regrowth after grazing resulted in delayed senescence, causing higher ET on the GR site.
Keywords: Evapotranspiration; Tallgrass prairie; Grassland; Energy balance; Energy fluxes; Bowen ratio; Latent heat flux